Differential Pulse Voltammetry: Evolution of an In Vivo Methodology and New Chemical Entries, A Short Review - Crespi Francesco (Journal of New Developments in Chemistry, 2020)
This short review tracks advances in differential pulse voltammetry for in vivo applications. It summarizes electrode designs, analyte scope, and calibration strategies, and outlines challenges for selectivity and biocompatibility.
Keywords: vivo methodology